4. Glutamatergic Findings in Schizophrenia: How to Make Sense of Them? - Lahti, Adrienne (Schizophrenia bulletin, 2017)
Overall Abstract: For the past 15 years, researchers have used proton magnetic resonance spectroscopy (1H-MRS) to characterize glutamatergic alterations in schizophrenia. Unfortunately, there is little consensus about what has been learned so far. Because of long acquisition time, the number of voxels from which measurements can be obtained is restricted. As more than 15 different brain regions have been evaluated, information on any specific region is limited. In addition, studies have used different field strengths, sequences, and spectral fitting methods. Importantly, vastly varying patient populations have been enrolled: chronic or first-episode patients and medicated, unmedicated, or medication-naive patients, leaving little chance to draw meaningful conclusions. There is a need to clarify what has been learned from well-characterized populations using rigorous methods and analyses. This session will present data collected from specific populations that address important questions regarding glutamate function in schizophrenia: relation to age, cognition, treatment response to antipsychotic medication, and other imaging modality. The session will also discuss the use of functional MRS that allows the measurements of changes in glutamate during cognition. Laura Rowland from the Maryland Psychiatric Research Center in Baltimore will present the results of studies that enrolled young and older subjects and showed effects of age and diagnosis on glutamate levels as well as significant relationship with cognitive function. Camilo de la Fuente Sandoval from the Instituto Nacional de Neurologia y Neurocirugia in Mexico City will present data collected in the associative striatum in first-episode, medication-naive patients, before and after antipsychotic treatment that found higher glutamate levels in patients resistant to first-line antipsychotic treatment. Adrienne Lahti from the University of Alabama at Birmingham will present a combined MRS/resting state functional magnetic resonance imaging study in unmedicated patients before and after treatment showing baseline abnormalities in both modalities that were associated with subsequent treatment response. James Stone from the Imperial College in London will present data collected during an n-back task showing abnormal dynamic modulation of glutamate in chronic patients compared to healthy volunteers. Larry Kegeles from Columbia University will lead a final discussion.